A novel hybrid construction of MnMoO4 nanorods anchored graphene nanosheets; an efficient electrocatalyst for the picomolar detection of ecological pollutant ornidazole in water and urine samples. (June 2021) - Venkatesh, Krishnan; Rajakumaran, Ramachandran; Chen, Shen-Ming; Karuppiah, Chelladurai; Yang, Chun-Chen; Ramaraj, Sayee Kannan; Ali, Mohammad Ajmal; Al-Hemaid, Fahad M.A.; El-Shikh, Mohammad Suliman; Almunqedhi, B.M.A.
Abstract: Nitroimidazole compounds are widely used antibiotics to encounter anaerobic bacterial and parasitic infections. The wide usage of antibiotic drugs became an ecological contaminant which in turn into potential monitoring. In this regards, we have designed and developed a new electrochemical sensing probe to monitor an antiprotozoal drug, ornidazole (ODZ), with the aid of a glassy carbon electrode (GCE) integrated with manganese molybdate nanorods (MnMoO4 ) decorated graphene nanosheets (GNS) hybrid materials that prepared by feasible probe sonochemical method (parameters: 2–4 W, 5 mV amp, 20 kHz). The electrochemical investigations of the developed probe were performed by using rapid scan electrochemical workstations namely cyclic voltammetry (CV) and amperometric (i-t) techniques. The as-prepared MnMoO4 /GNS nanocomposite was characterized and its purity of nanocomposite formation was confirmed by various analytical techniques like X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and Raman spectroscopy. In addition to that, the textural morphology of the MnMoO4 /GNS nanocomposite was examined with the aid of field emission scanning electron microscopy (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM). The MnMoO4 /GNS nanocomposite rotating disk glassy carbon electrode (RDGCE) plays a crucial role in electrochemical detection of ODZ, which results in excellent anti-interference ability, a lower detection limit of 845 pM, massive linear ranges from 10 to 770 nM, and good sensitivity of about 104.62 μA μM −1 cm −2 . From the acquired electrochemical studies, we have developed a disposable electrochemical sensor probe using a low-cost screen-printed carbon electrode (SPCE) with MnMoO4 /GNS nanocomposite. The MnMoO4 /GNS/SPCE are capably employed in real-time sensing of ODZ in water and urine samples. These electrochemical studies revealed the integral new vision on the electrocatalytic performance of the modified SPCE and also shown excellent amplification results in ultra-trace levels. Graphical abstract: Image 1 Highlights: A robust electrochemical sensor probe for ornidazole (ODZ) detection has been reported. The MnMoO4 decorated graphene nanosheets (GNS) hybrid catalyst prepared by probe sonication method. The MnMoO4 /GNS electrocatalyst showed trace-level detection limit around 845 pM. The developed sensor was employed for real-time sensing of ODZ in water and urine samples.